2020
DOI: 10.1093/ndt/gfaa158
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium zirconium cyclosilicate increases serum bicarbonate concentrations among patients with hyperkalaemia: exploratory analyses from three randomized, multi-dose, placebo-controlled trials

Abstract: Background Sodium zirconium cyclosilicate (SZC) binds potassium and ammonium in the gastrointestinal tract. In addition to serum potassium reduction, Phase 2 trial data have shown increased serum bicarbonate with SZC, which may be clinically beneficial because maintaining serum bicarbonate ≥22 mmol/L preserves kidney function. This exploratory analysis examined serum bicarbonate and urea, and urine pH data from three SZC randomized, placebo-controlled Phase 3 studies among patients with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…These observations are consistent with those from phase III SZC studies of patients with hyperkalemia. 29 The observed increase in serum bicarbonate is likely due to SZC binding of gastrointestinal ammonium, while decreases in serum urea are associated with SZC effects on serum bicarbonate. 29 Indeed, these findings in healthy volunteers are of note as maintaining serum bicarbonate ≥22 mmol/L is a major goal for the treatment of CKD.…”
Section: Discussionmentioning
confidence: 96%
“…These observations are consistent with those from phase III SZC studies of patients with hyperkalemia. 29 The observed increase in serum bicarbonate is likely due to SZC binding of gastrointestinal ammonium, while decreases in serum urea are associated with SZC effects on serum bicarbonate. 29 Indeed, these findings in healthy volunteers are of note as maintaining serum bicarbonate ≥22 mmol/L is a major goal for the treatment of CKD.…”
Section: Discussionmentioning
confidence: 96%
“…11 Several Phase III studies confirmed the mild increase in serum bicarbonate levels with SZC, and a later path analysis performed in a metaanalysis showed that the probable cause for this increase in bicarbonate was ammonium absorption by SZC in the gut. 12 The Phase III studies also confirmed that SZC decreased serum urea levels in a dose-dependent manner, with the highest doses causing a decrease of 15%-20%. 13,14 In end-stage renal disease (ESRD) patients oral SZC can effectively decrease high pre-dialysis potassium levels in patients on 3/week dialysis.…”
mentioning
confidence: 69%
“…Probably the pinnacle of my career was my 2013 presentation on Phase II and III trials during the “Late Breaking Clinical Trials” session at the American Society of Nephrology (ASN) 11 . Several Phase III studies confirmed the mild increase in serum bicarbonate levels with SZC, and a later path analysis performed in a meta‐analysis showed that the probable cause for this increase in bicarbonate was ammonium absorption by SZC in the gut 12 . The Phase III studies also confirmed that SZC decreased serum urea levels in a dose‐dependent manner, with the highest doses causing a decrease of 15%–20% 13,14 .…”
Section: Figurementioning
confidence: 82%
“…The impact of SZC dose on serum bicarbonate was not assessed here; however, increases in serum bicarbonate levels have been shown with SZC in a dose-dependent manner in Phase 3 studies of patients with hyperkalemia. 9 Indeed, in patients on maintenance dialysis in DIALIZE, similar increases from baseline in serum bicarbonate were observed with SZC overall at Day 57 (mean [SD]: SZC +0.5 1 This observed increase in serum bicarbonate is likely due to SZC binding of gastrointestinal ammonium. The impact of dose titration in each SZC dose group and the post hoc nature of the analysis should be considered when interpreting these findings.…”
mentioning
confidence: 73%